Cenozoic Exhumation and Deformation of the Intermontane Pastos Chicos Basin in the Southern Central Andes: Implications for the Tectonic Evolution of the Andean Plateau (Puna) and the Eastern Cordillera Between 23° and 24°S, NW Argentina. Issue 2 (3rd February 2023) - Pingel, Heiko; Deeken, Anke; Coutand, Isabelle; Alonso, Ricardo N.; Riller, Ulrich; Sobel, Edward R.; Cottle, John M.; Strecker, Manfred R.
Abstract: The Andean Plateau of north‐western Argentina (Puna) at a mean elevation of ca. 4.2 km constitutes the southern continuation of the Altiplano; it is a compressional basin‐and‐range province comprising fault‐bounded, high‐elevation mountain ranges and largely internally drained basins with often thick sedimentary and volcaniclastic fill. Growing sedimentological and structural evidence supports the notion that the north‐western Argentine Andes between 22° and 26°S developed from an initial extensive broken‐foreland system that extended across the present‐day eastern Andean flank during the early to middle Eocene. However, compelling evidence of the tectonic history of this region is still missing. Here, we present new apatite fission track and zircon (U–Th)/He thermochronological data and U–Pb zircon ages from intercalated volcanic ash deposits from the Pastos Chicos Basin (23.5°S, 66.5°W) to constrain basin formation and the timing of major crustal deformation in the northern Puna. Inverse thermal modeling of the thermochronological data provides further temporal constraints on the late Cenozoic cooling history of the crust in this region and, by inference, on the timing of upper‐crustal shortening, range uplift, and basin formation in the northern sector of the present‐day Puna Plateau. Specifically, we argue for plateau‐wide distributed deformation in the Eocene between 23° and 24°S, followed by spatially disparate and diachronous deformation (Oligocene to Pliocene). Plain Language Summary: The Argentine Puna Plateau is a mountainous region in the Central Andes of South America. It is the result of the tectonic convergence between the oceanic Nazca Plate and the continental South American Plate. However, the detailed tectonic evolution of this region is yet unknown. We present new thermochronologic data from the Puna Plateau that allow inferences about crustal deformation and mountain range uplift. Combined with previous studies, our results suggest deformation distributed over the entire plateau during the Eocene. Thereafter, local deformation occurred spatially non‐systematic, possibly related to zones of weakness in the crust. Key Points: Thermal modeling of apatite fission track and (U‐Th)/He zircon data from the Pastos Chicos Basin shows Oligo‐Miocene onset of exhumation Regional compilation of spatio‐temporal deformation at 23°–24°S suggests out‐of‐sequence deformation related to basement heterogeneities Mio‐Pliocene U–Pb zircon ages of volcanic ash deposits refine the chronostratigraphy of the Pastos Chicos Basin